1996
DOI: 10.1037/0022-006x.64.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Preventing hung juries about therapy studies.

Abstract: A series of arguments are presented that emphasize the importance of comparatively evaluating psychotherapies with appropriate pharmacotherapy and pill placebo. The lack of a pill-placebo arm has rendered moot those studies that compared pharmacotherapy directly with psychotherapy because of the lack of an internal sample defining calibration with regard to medication responsivity. The National Institute of Mental Health (NIMH) Treatment of Depression Collaborative Research Program is critically discussed beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1
6

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 9 publications
2
91
1
6
Order By: Relevance
“…In most naturalistic follow-ups, patients not only must complete treatment but must show improvement to be retained in the sample. If one treatment is more effective than another in keeping high-risk patients in treatment or in eliciting their response, then acute treatment can act as a differential sieve that undermines the effects of initial randomization ( Klein, 1996 ). For example, several studies have suggested that patients treated to remission with cognitive therapy are about half as likely to relapse after treatment termination as patients who respond to pharmacotherapy ( Hollon et al, 1991 ).…”
Section: Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…In most naturalistic follow-ups, patients not only must complete treatment but must show improvement to be retained in the sample. If one treatment is more effective than another in keeping high-risk patients in treatment or in eliciting their response, then acute treatment can act as a differential sieve that undermines the effects of initial randomization ( Klein, 1996 ). For example, several studies have suggested that patients treated to remission with cognitive therapy are about half as likely to relapse after treatment termination as patients who respond to pharmacotherapy ( Hollon et al, 1991 ).…”
Section: Follow-upmentioning
confidence: 99%
“…Although this design allows the investigator to avoid assigning some clients to conditions he or she believes will be inferior, the resultant data are inherently difficult to interpret. One concern is that the evaluator needs to be confident that the established comparison treatment was implemented well in the particular study; otherwise, the unproven treatment will erroneously be deemed efficacious by comparison with a degraded version of the more established treatment ( Klein, 1996 ). Another common problem is low statistical power.…”
Section: Comparisons With Other Treatments or With Placebomentioning
confidence: 99%
See 1 more Smart Citation
“…Así, Klein (1996) concluyó que la imipramina tuvo efectos más beneficiosos en pacientes con depresión más grave, mientras que Jacobson y Hollon (1996) señala-ron que los pacientes tratados con imipramina abandonaron con mayor frecuencia el tratamiento y presentaron más recaídas y, por otra parte, estos últimos autores señalaron que todos los trabajos publicados han encontrado una superioridad de la terapia cognitiva frente a los fármacos en el tratamiento de la depresión. A todo ello hay que añadir la carencia de información respecto a las interacciones multivariable que se presentan en el análisis de casos reales y complejos como son las depresiones.…”
Section: El Problema De La Valoración De Las Terapias Psicológicas: Uunclassified
“…This variability greatly limited our freedom to make assumptions about the placebo response rate in any new study context. It is for this reason that Klein [77] concluded that any investigation comparing psychosocial interventions to an established antidepressant medication (representing the 'standard of care') must include a pill-placebo condition in order to assure that the patient sample is actually one that is responsive to the medication beyond the effects of a placebo. Unless a superiority of medication to pill-placebo can be demonstrated in the current study, it could be maintained that these patients were not medication-responsive and that any observed treatment effects would be open to parsimonious explanation as a placebo response.…”
Section: The Use Of a Placebo Control Groupmentioning
confidence: 99%